A methodology for assessing geographical information science professionals and programmes in South Africa - Du Plessis, Hendrik Jacobus (Stellenbosch : Stellenbosch University, 2015)
ENGLISH ABSTRACT: There is a growing demand worldwide for geographical information science (GISc) practitioners. Government agencies and the private sector are competing to find and employ practitioners in the GISc field who are suitably qualified and competent in the practice of the relevant technologies and sciences. Little research exists in South Africa on what GISc professionals should know or be able to do. A set of competencies, knowledge and skills required by professionals in the workplace is needed to design appropriate programmes and to guide those responsible for controlling quality in the profession (through registration) as well as in educational institutions (through accreditation). This research developed a new GISc academic framework with an embedded competency set to serve as a standard for the training of professional GISc practitioners. The format of this GISc framework is based on the structure of the University Consortium of Geographical Information Science (UCGIS) geographical information science and technology (GI S&T) body of knowledge (BoK) as the most frequently used framework internationally, but incorporates content from two existing South African competency sets. The new framework represents the South African, the USA and European perspectives of the knowledge and skills regarded as essential for the GISc profession. An easy-to-use and accessible web-based GISc self-assessment tool (SAT) was developed to facilitate the implementation and adoption of the new framework. Based on feedback from the GISc community the tool is proving to be a valuable labour- and time-saving resource with significant benefits to the GISc society and academia. The new GISc framework, which consists of 14 knowledge areas, 6 fundamental and 32 core units, was developed using a combination of qualitative and quantitative procedures to compare three different existing competency sets. This methodology is unique and lends itself for application in similar studies regardless of the discipline. Through the literature studied, no other GISc web-based SAT was discovered, making the concept of a web-based and database driven SAT unique. The SAT can be modified for use in other disciplines and countries.